Teleducation: medical education in the pandemic and beyond - Soong, Tse Kiat; Ng, Lloyd Jee Hean; Lau, Joel Wen Liang; Chong, Choon Seng; Lee, James Wai Kit (Frontiers in Medicine, 2023)
Medical education in the pandemic has been challenging owing to various physical and technological constraints in the current education landscape. This has resulted in reduced patient contact and opportunities for clinical exposure. In utilizing various platforms to supplement teaching, we adopted the use of Telegram, a cloud-based messaging application as an education aid for 3 cohorts of medical students in 1 medical school in Singapore. Herein, we share our experience with Telegram as a novel platform to augment medical education and to supplement clinical training amidst the various constraints. We believe that the circumstances have allowed us to find a method that may serve as an effective adjunct in education. Qualitative feedback has been positive and generally in line with our goals. We believe that further work could involve utilizing other features of the application, or by developing specialized applications to serve the same purpose. More needs to be done to consider applicability in different cultural and socioeconomic contexts.